Foundation and development of the department of surgical dentistry and maxillofacial surgery of Bukovinian State Medical University - Halahdina, Alla; Gerasym, Lalita (Journal of Education, Health and Sport, 2019)
The article highlights the foundation and development of the department of surgical dentistry and maxillofacial surgery of Bukovinian State Medical University.